Compliance to iron folic acid supplementation among antenatal women attending antenatal clinic in North Kerala: a cross-sectional study - Muniaraj, Reshma; Kumaran , Jayasree Anandabhavan (International Journal Of Community Medicine And Public Health, 2025)
Background: Anemia is a common condition among antenatal women, and the most significant cause of it is iron deficiency. Many countries, including India, have policies to provide iron supplements to them. However, noncompliance is a major obstacle in fighting anemia. Objective was to determine the compliance to iron folic acid supplements and its influencing factors among an antenatal women attending antenatal clinic in a secondary level health care centre in north Kerala. Methods: A cross-sectional study was conducted among 110 antenatal women attending antenatal clinic in a secondary level health centre in Kannur. Subjects were recruited through consecutive sampling. Data was collected by direct interview using a semi structured questionnaire. Missing >2 doses consecutively was considered as noncompliance. Data was analysed using SPSS 21. Chi-square and Fisher’s exact tests were used to find the association of compliance. A p value <0.05 was considered significant. Results: The mean age of the study population was 26.5±4.59 years. The compliance to IFA supplementation was 79%. Noncompliance was mainly due to forgetfulness (52%) and side effects (44%). Among antenatal women with comorbidities, 61.5% had less compliance compared to those without comorbidities and is statistically significant (p value <0.01). Antenatal counselling had a significant association with compliance (p value <0.001). Antenatal women who received counselling (85.6%) were more compliant. Conclusions: The compliance to IFA supplementation among antenatal women was 79%. Forgetfulness and side effects were the main factors for noncompliance. The presence of comorbidities was significantly associated with lower compliance, and antenatal counselling was strongly linked to improved compliance.